The influence of knowledge management on new product development performance in Malaysian multimedia super corridor companies - Lau, King Nim (Universiti Malaysia Sarawak (UNIMAS), 2014)
Malaysia’s plan to achieve “developed country” status depends on it sustaining high economic growth across a wide range of industry sectors. But this growth cannot be maintained in such a competitive global environment without developing Malaysia’s manufacturing-based economy to be knowledge-based. Success in a knowledge-based global economy depends on a country’s ability to develop and manage its knowledge, and in particular how organisations’ acquire, disseminate and respond to knowledge. To contribute to an increasingly important body of knowledge in the Malaysian context, this study investigates the influence of knowledge management on new product development performance in Multimedia Super Corridor companies located in Malaysia. Specifically, the purpose of this study is to (a) find out the influence of knowledge acquisition and its dimensions, employee attitudes and opinions, financial reporting systems, and sensitive to market place information, on new product development performance; (b) examine the influence of knowledge dissemination and its dimensions, knowledge disseminated on the job, disseminate knowledge technique, and disseminate knowledge technology, on new product development performance; and (c) investigate the influence of responsiveness to knowledge and its dimensions, respond to customer, respond to technology, and flexibility and opportunistic, on new product development performance in Malaysian Multimedia Super Corridor companies.